2020
DOI: 10.1016/j.compositesa.2020.105803
|View full text |Cite|
|
Sign up to set email alerts
|

Swelling of natural fibre bundles under hygro- and hydrothermal conditions: Determination of hydric expansion coefficients by automated laser scanning

Abstract: The effect of humidity conditions on the moisture content and dimensional variations of natural fibre bundles from several botanical origins with contrasting biochemical and structural characteristics is investigated. Results highlight wide variations in water uptake and swelling behaviour of fibre bundles according to plant species. Two main swelling mechanisms are identified: (i) a microscopic swelling due to the sorption of bound water in the cell walls and the middle lamella, and (ii) a macroscopic swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Water pretreatment generates a water uptake by the fibers, which occurs under two states in natural fibers, depending on the moisture content [ 22 , 27 , 28 ]: (i) Water bound to the different biopolymers constituting the cell walls and middle lamella, involving the formation of hydrogen bonds with hydroxyl groups OH, and (ii) free water that fills voids (micro- and macropores of cell walls and lumens) and is retained by capillary forces. Garat et al [ 29 ] measured moisture content of 62.8 ± 0.7% for hemp fiber bundles in immersion (compared to 60.9 ± 0.7% for flax fiber bundles). Moreover, Pejic et al [ 28 ] showed that lignin removal decreases the moisture sorption and increases the water retention ability of hemp fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water pretreatment generates a water uptake by the fibers, which occurs under two states in natural fibers, depending on the moisture content [ 22 , 27 , 28 ]: (i) Water bound to the different biopolymers constituting the cell walls and middle lamella, involving the formation of hydrogen bonds with hydroxyl groups OH, and (ii) free water that fills voids (micro- and macropores of cell walls and lumens) and is retained by capillary forces. Garat et al [ 29 ] measured moisture content of 62.8 ± 0.7% for hemp fiber bundles in immersion (compared to 60.9 ± 0.7% for flax fiber bundles). Moreover, Pejic et al [ 28 ] showed that lignin removal decreases the moisture sorption and increases the water retention ability of hemp fibers.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Sawpan et al [ 24 ] and Sair et al [ 33 ] observed an increase of tensile properties for hemp fibers after alkali treatments that they attributed to a relaxation and reorganization of the microfibrils along the principal axis of the fiber, resulting in a more rigid structure thanks to the elimination of lignin and hemicellulose components. Besides a reduction of lignin and hemicellulose amounts [ 29 , 30 ], authors report a transformation of cellulose II to cellulose I [ 33 ] and an augmentation of the cellulose crystallinity [ 31 ] after application of an alkaline pretreatment to the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray tomography conducted on a single wood fibre by Joffre et al [38] showed dimensional changes when increasing the ambient relative humidity from 47% to 80%, but without focusing on the lumen shape. Garat et al [8] determined a decrease of the form factor of flax bundles under increasing relative humidity conditions. In these cases, the fibres might swell in an anisotropic way partly to recover their in-planta rehydrated and more circular state.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, porosities in plant fibres are also the location of free water filling at high moisture content. This water is involved in the hydric expansion coefficients of the fibre, and, in other words, determines its dimensional characteristic [8] and related hygromorph properties [9]. From an engineer or material scientist point of view, porosity is an important characteristic of plant fibres to deal with in order to tailor Fibers 2021, 9, 24 2 of 17 plant fibre composites.…”
Section: Introductionmentioning
confidence: 99%
“…The exposure causes aging, which needs to be studied to evaluate their behavior during their service life. In general, the dimensional stability of the composites and their mechanical performance are strongly influenced by hygro-thermal and hydro-thermal conditions, which are related to relative humidity and immersion conditions, respectively [ 97 ]. The ability of natural fibers to absorb moisture relies on the hydrophilic nature of the fibers itself.…”
Section: Factors Determine the Mechanical Failurementioning
confidence: 99%